Development of Programming-based TPACK Education Program through Design-based Research - Kim, Seong-Won; Lee, Youngjun (韓國컴퓨터情報學會論文誌, 2019)
As the importance of technology in education has increased, TPACK research has been actively conducted to promote the use of technology in class. However, due to the functional limitations of technology, the pre-service teacher had difficulty in using technology in class. Therefore, in this study, we have been studying the introduction of the programming language as a technology tool of TPACK. Using design-based research as a research method, we repeatedly developed an educational program, applied to pre-service teachers, and evaluated the effectiveness of the program. In the first study, pre-service teachers had difficulties in programming learning. To solve this problem, programming-based instruction and curriculum analysis were supplemented by educational programs. In the second study, pre-service teachers felt difficulty in using programming in teaching-learning, thus improving instruction design and reflection. The third study enhanced the programming development environment search to supplement programming learning and utilization. 교육에서 테크놀로지의 중요성이 증가함에 따라 수업에서 테크놀로지 활용을 촉진하기 위하여 TPACK 연구가 활발하게 진행되었다. 하지만 테크놀로지가 가진 기능적인 한계로 인하여 예비 교사는 수업에서 테크놀로지 활용에 어려움을 겪고 있었다. 따라서 본 연구에서는 기능적 한계가 존재하지 않는 프로그래밍 언어를 TPACK의 테크놀로지 도구로 도입하는 연구를 진행하였다. 연구 방법으로 설계 기반 연구를 활용하여, 교육 프로그램을 개발하고, 예비 교사를 대상으로 적용하고, 효과를 평가하는 연구를 반복하여 진행하였다. 1차 연구에서는 예비 교사가 프로그래밍 학습에 어려움을 겪었으며, 이를 해결하기 위하여 프로그래밍 기반 수업과 교육과정 분석을 교육프로그램에 보완하였다. 2차 연구에서는 교수-학습에서 프로그래밍의 활용에 어려움을 느껴서, 수업 설계 및 성찰을 보완하였다. 3차 연구에서는 프로그래밍 학습 및 활용을 보완하기 위하여 프로그래밍 개발 환경 탐색을 보완하였다.